Perception of spirituality and spiritual care among undergraduate nursing student in Puncak Alam / Faseeha Ismail and Nur Suhaili Mohd Nor - Ismail, Faseeha; Mohd Nor, Nur Suhaili (2018)
The growing of spirituality has been started over the past 30 years with the recognition of the importance of spirituality in nursing field, but there is lack of research on how spirituality is being understood, taught and applied by student nurse who will later take nursing as their profession. This study conducted to determine spirituality perception and association of demographic with spirituality care in order to build a holistic nurse. A cross sectional study was conducted towards one hundred and eight respondents in Faculty of health sciences in UiTM Selangor, Kampus Puncak Alam. The respondent are selected among four batches of undergraduate nursing students. The questionnaire given are Spiritual Care Giving Scale (SCGS) that was adapted from Tiew et al., (2013), a self-administered question about perspective of spirituality and spiritual care of undergraduate nursing students. Finding of this research found that nursing students in Puncak Alam convey agreement in perception of spirituality by overall mean value SCGS 4.00. Researcher found that there are positive association between demographic data and perception towards spirituality on dichotomous question only. Therefore, the result show that perception of spirituality and spiritual care are high in nursing students of UiTM Puncak Alam. It is also proven that there are association of spirituality care and demographic data. Thus, this study suggest that age, gender and year of study are not associated with perception towards spirituality and spiritual care. Thus, it is important to re-evaluate the nursing syllabus in order to provide more knowledge and practice about spiritual care for the students.